Reduced postburn hypertrophic scarring and improved physical recovery with yearlong administration of oxandrolone and propranolol - Herndon, David; Capek, Karel; Ross, Evan; Jay, Jayson; Prasai, Anesh; Ayadi, Amina; Foncerrada-Ortega, Guillermo; Blears, Elizabeth; Sommerhalder, Christian; McMullen, Kara; Amtmann, Dagmar; Cox, Robert; et al. (Annals of surgery, 2018)
Background:Massive burns induce a hypermetabolic response that leads to total body wasting and impaired physical and psychosocial recovery. The administration of propranolol or oxandrolone positively affects postburn metabolism and growth. The combined administration of oxandrolone and propranolol (
Publication Date: September 2018
Gesehen am 18.12.2019